(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This article reveals the meaning of the concept of "patriotism", describes the problematic issues associated with an increase in the feeling of patriotism among young people, the conditions and reasons for these issues, as well as possible ways to solve them.